Impact of cell spreading on second‐life of lithium‐ion batteries. (12th September 2022) - Galatro, Daniela; Romero, David A.; Da Silva, Carlos; Trescases, Olivier; Amon, Cristina H.
Abstract: The evolution of the degradation paths of the cells in battery packs is shaped by both intrinsic cell‐to‐cell variations, also known as cell spreading, and spatial–temporal cell‐to‐cell differences in temperature and other stress factors. To account for these variations and differences in degradation, we propose a statistical approach for modelling the degradation of lithium‐ion batteries (LIBs) that utilizes a three‐parameter non‐homogeneous gamma process, allowing for the prediction of the capacity fade or time‐to‐failure for any LIB architecture. This degradation modelling approach has been integrated into a cost model to investigate the sensitivity of the battery lifetime's economic outcome, aiming to maximize the added value of stationary battery storage composed of degraded electric vehicle batteries. Thus, the impact of cell spreading was quantified for three simulation scenarios on second‐life applications: (i) performing a simplified cost analysis to evaluate the business case for second‐life, (ii) performing an economic analysis to visualize the impact of spreading, and (iii) evaluating an existing power flow control strategy between LIB modules. The information derived from the spreading‐cost integration approach is valuable to support the technical and economic analyses in the decision‐making process of designing, installing, and running efficiently second‐life applications.